LEXICOLOGY AND PHRASEOLOGY AS A SYSTEM OF LANGUAGE ELOQUENCE - Jabborova Gulchehra (Journals Park Publishing, 2023)
This article discusses how rich the Russian language is, the role of lexicology and phraseology in our speech, how many words great writers used in their works, the features of phraseological units, the phenomena of antonymy and synonymy in phraseology, the differences between a word and a phraseological unit.
Keywords: lexicology, phraseology, lexical richness of the language, linguistic dictionary, synonymy, antonymy.